TOG: A Model for Innovation-Centric Design in Games and Expressive Interactive Media - Eladhari, Mirjam Palosaari; Koenitz, Hartmut (Transactions of the Digital Games Research Association, 2021)
This paper describes an approach to facilitate innovation in game design by increasing the designers’ palette of playable and participatory computational expressions. The TOG model (Technology, Ontology, and Game Genre) can be used in teaching game design and related practices, but is also applicable to prototyping in professional settings. TOG is inspired by the processes of AI-based game design, and introduces the concept of the techno-artistic minimum. It was conceptualized when teaching a course on computational expression at Malta University. The main aim for teaching with the TOG model was to facilitate innovation by challenging aspiring game designers to think ‘outside the box’ and come up with unusual and innovate creative solutions. In addition, TOG can complement existing design methods such as MDA and DDT in the practice of professional game designers.